Strategi Pengembangan UMKM Perajin Dupa di Desa Dalisodo, Wagir, Kabupaten Malang dengan Pendekatan Analisis SWOT & QSPM - Yoga, Tirta; Khoirunnisa’, Ninin (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
MSMEs have a significant contribution in driving local and national economic growth, including in creating jobs and improving community welfare. One of the growing agribusiness-based MSMEs is the incense craftsman business in Dalisodo Village, Wagir District, Malang Regency. This study aims to produce alternative strategies and priority strategies for the development of the Dalisodo incense business. There are three main respondents in this study, namely the owners or business actors of incense craftsmen. Data were analyzed using SWOT and QSPM. SWOT and QSPM analysis were used to produce alternative strategies and priority strategies. The results of the analysis place business actors in a growing and developing position with an aggressive quadrant I. Furthermore, three priority strategies were produced, namely: 1) Optimizing product quality and loyal customer networks to expand the market outside Bali and for export; 2) utilizing good relationships between craftsmen and price stability to increase product capacity and dominate the local market; 3) improving production risk management through QC training and stock management. With the implementation of the right strategy, the Dalisodo incense MSME is able to increase its competitiveness and business sustainability in facing market dynamics.